2019
DOI: 10.3389/fpsyt.2019.00236
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive Remediation in Early Versus Chronic Schizophrenia: A Preliminary Report

Abstract: Background: Many evidences have demonstrated the effectiveness of cognitive remediation on cognition and functioning in patients with schizophrenia. Some researchers speculate that cognitive deficits are more amenable to remediation during earlier phases of illness than in chronicity. Therefore, cognitive rehabilitation should be used as an early intervention, seeking to produce durable functional changes in the early course of schizophrenia. Although there is strong evidence that cognitive remediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…Moreover, some preliminary animal modeling suggests that the adolescent brain may be better able to learn from cognitive training 60 as a function of the unique neurobiology of adolescence (e.g., reward hypersensitivity). Further, accumulating evidence suggests that cognitive remediation in early phases of illness may yield greater than when applied in chronic phases 61,62 . Our results suggest that cognitive flexibility may represent a meaningful and transdiagnostic target for cognitive remediation, which may be enhanced when offered to young people early in the course of illness alongside other interventions targeting social and occupational functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some preliminary animal modeling suggests that the adolescent brain may be better able to learn from cognitive training 60 as a function of the unique neurobiology of adolescence (e.g., reward hypersensitivity). Further, accumulating evidence suggests that cognitive remediation in early phases of illness may yield greater than when applied in chronic phases 61,62 . Our results suggest that cognitive flexibility may represent a meaningful and transdiagnostic target for cognitive remediation, which may be enhanced when offered to young people early in the course of illness alongside other interventions targeting social and occupational functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Illness onset was evaluated by the Nottingham Onset Schedule 23 with the information provided by the patients, other family members, and other sources. Patients with a duration of illness longer than 5 years were defined as "chronic" 24,25 . Symptom severity assessment was carried out using the Positive and Negative Syndrome Scale (PANSS) 26 on the same day as MRI scanning.…”
Section: Participantsmentioning
confidence: 99%
“…In a recent meta-analysis, effect sizes for global cognitive improvement were somewhat larger for chronic schizophrenia compared to early schizophrenia [511]. Conversely, other studies have reported that younger, less chronic patients receiving lower doses of antipsychotic medication respond best to these types of intervention [512,513].…”
Section: Cognitive Remediation Therapymentioning
confidence: 93%